Seasonal influenza vaccines and hurdles to mutual protection. (1st December 2016) - Chiu, C.
Abstract: While vaccines against seasonal influenza are available, major hurdles still exist that prevent their use having any impact on epidemic spread. Recent epidemiologic data question the appropriateness of traditional vaccination timing (prior to the winter season) in many parts of the world. Furthermore, vaccine uptake in most countries even in high-risk populations does not reach the 75% target recommended by the World Health Organization. Influenza viruses continually undergo antigenic variation, and both inactivated and live attenuated influenza vaccines confer only short-lived strain-specific immunity, so annual revaccination is required. Improving vaccine-induced immunity is therefore an important goal. A vaccine that could confer durable protection against emerging influenza strains could significantly reduce onward transmission. Therefore, further understanding of protective immunity against influenza (including broadly cross-protective immune mechanisms such as haemagglutinin stem-binding antibodies and T cells) offers the hope of vaccines that can confer the long-lived heterosubtypic immune responses required for mutual protection.